La actuación inmediata de las sentencias condenatorias en el Perú, ¿compatible con la presunción de inocencia y el derecho al recurso? - Valenzuela Ylizarbe, Fredy (2024)
This article examines the suspensive effect of appeals against convictions, highlighting its impact on the protection of fundamental rights such as the presumption of innocence. The need to suspend the execution of the sentence until it becomes final is analyzed and measures to avoid undue delays are explored. In addition, the application of this principle in the criminal and civil spheres is reviewed, highlighting the differences and challenges in its implementation. In conclusion, the article provides a critical and detailed analysis of the regulation of the suspensive effect, highlighting its relevance for equitable and effective justice.